Nano casein–pectin complex: exploring physicochemical, organoleptic properties, and LAB viability in skimmed milk and low-fat yoghurt - Gomaa, Mohamed A. E.; Allam, Marwa G.; Mokhtar, Esraa; Ayad, Eman H. E.; Darwish, Saeid M.; Darwish, Amira M. G. (Frontiers in Nutrition, 2024)
Protein complexes with a nutritional value, heat stability, and gelling properties with no negative impact on culture viability have promising application prospects in the fermentation industry. The aim of the study was to investigate the possibility of applying physical modification seeking high-protein-fortified yoghurt production using the nano casein–pectin NCP complex as an active colloidal system with enhanced structural and thermal properties and monitor the quality properties of the physicochemical, heat stability, rheological, starter culture viability and sensory evaluation of fortified products comparing with the plain control throughout the cold storage. High-energy ball milling (HEBM) technique was used to produce nanoparticles of casein powder and smaller particles of pectin individually, and particle size and zeta potential was assessed. Deferent Nano casein-pectin (NCP) complex formulations were prepared, their physicochemical properties were assessed including protein quality via Amino Acid Analyzer (AAA), viscosity, thermogravimetric analysis (TGA), and then used in fortification of skimmed milk and low-fat yoghurt to monitor the fortification effects. The particle sizes showed to be ≈166 nm and 602.6 nm for nano-casein and pectin, respectively. Milk fortification with the NCP complex has significantly increased the nutritional value represented in increased protein content (7.19 g/100 g in NCP5); Ca, P, and S content (2,193.11, 481.21, and 313.77 ppm); and amino acid content with first limiting amino acids; histidine (0.89 mg/g), methionine (0.89 mg/g), and low content of hydrophobic amino acids (HAAs) may cause aggregation. NPC fortification enhanced physicochemical properties announced in enhanced viscosity (62. mP.s in NCP5) and heat stability (up to 200°C) compared with control skimmed milk (SM). NCP yoghurt fortification significantly increased protein content to 11 mg/100 g in T5, enhanced viscosity to 48.44 mP.s in T3, decreased syneresis to 16% in T5, and enhanced LAB viability which was translated in preferable sensorial properties. Applying fortification with nanoparticles of the casein–pectin (NCP) complex balanced the amino acid content and improved physicochemical, rheological, nutritional, and sensorial properties and LAB viability, which can be recommended further in functional food applications.